Post-Keynesian stock-flow models after the subprime crisis: the need for micro-foundations - Photis Lysandrou (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2014)
The subprime crisis exposed a flaw in post-Keynesian stock-flow models, namely their concession to mainstream macroeconomic theory that financial markets obey a price-clearing rule. Two reasons lie behind this concession. The first is the assumption that investors give priority to the price dimension of securities and only secondary importance to their quantity dimension. This paper argues that following recent structural changes in domestic economies the securities markets are now dominated by investors who give co-priority to the price and quantity dimensions of securities, for which reason these markets now operate to the same demand-led quantity adjustment process as do all other markets. The second and more fundamental reason is that post-Keynesian stock-flow models lack a micro-foundational unit of analysis from which can be derived an overarching methodological framework that is not only externally realistic but also internally coherent. This paper argues that the unit of analysis that best fits this purpose is the 'commodity', a term that will be used both exclusively, to denote only those entities that are priced to a market standard, and inclusively, to denote not only the outcomes of human activities but also the capacities for activity that are subject to pricing standards.
Keywords: E12; G01; 330; post-Keynesian stock-flow models; subprime crisis; micro-foundations; commodity